2016
DOI: 10.1111/bju.13451
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in positive surgical margin rate after laparoscopic radical prostatectomy by application of the modified surgical margin recommendations of the 2009 International Society of Urological Pathology consensus

Abstract: The impact of PSMs after LRP for prostate cancer remains unclear. PSMs in the present cohort of patients undergoing LRP had different characteristics and conferred different risks of BCR. A better understanding of PSM characteristics and a careful standardized pathological evaluation is needed to adequately counsel patients with respect to prognosis and adjuvant therapy after LRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It should, however, be noted that their study included patients classified N+ and/or pT3b, which could be confounding factors in the BR assessment. Similarly, Maxeiner et al [16] reported that multiple PSM and those > 3 mm represented an independent BR factor, whereas these authors likewise included patients with potential confounding factors (N+, PT3b, PT4, or neoadjuvant treatment).…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that their study included patients classified N+ and/or pT3b, which could be confounding factors in the BR assessment. Similarly, Maxeiner et al [16] reported that multiple PSM and those > 3 mm represented an independent BR factor, whereas these authors likewise included patients with potential confounding factors (N+, PT3b, PT4, or neoadjuvant treatment).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [27, 28] demonstrated that patients with PSMs have a higher risk of BCR and clinical progression but not necessarily of cancer-specific mortality. At a median follow-up of 92 months (IQR, 87–99), our BCR rate was 30% and cancer-specific mortality was 2%, both of which are within the range reported in recent studies [3–6, 8, 14, 1618, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings explain this controversy, which is likelydue to lack of distinction between focal and extensive PSMs at the apex. This further demonstrates the importance of adopting a standard method to report PSMs, including their precise extent and location [28]. The finding that focal apical PSMs are not associated with BCR is important, as it could help surgeons improve functional outcomes by sparing the sphincter, and could improve prognosis and decisions regarding additional radiotherapy (RT) [1, 2, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some had a low sample size and/or a short follow-up period [7,21,[25][26][27]. Maxeiner et al [28] also showed GS 8-10 increased risk of BCR in univariable analysis; however, they failed to perform a multivariable analysis due to insufficient sample size. Pettenati et al [29] used a logistic regression model for analysis and did not report multivariable Cox proportional hazards modelling.…”
Section: Discussionmentioning
confidence: 99%